Assessment of Construction Productivity in the Context of Khulna City of Bangladesh - Rakib, Md. Farhad Hossain; Hasan, Rakibul; Howlader, Sujan; Rahman, Mizanoor (Journal of Technology Management and Business, 2022)
This paper examines the current state of construction productivity in Khulna, Bangladesh and major factors that influence productivity. A questionnaire survey was distributed to various stakeholders and construction projects in Khulna city. Ten projects in Khulna were selected for productivity assessment and a total of 100 respondents participated for ranking the influencing factors. The data were then used to calculate the productivity and relative important index which enabled the factors to be ranked. Factors influencing construction productivity were analyzed using an RII method. The average productivity of formwork, concrete work, brickwork, and plastering work in the Khulna construction industry is 3.40 sqft/hr, 4.98 cft/hr, 1.82 cft/hr, and 8.16 sqft/hr respectively. Analysis of these factors showed that the top five ranked factors affecting construction productivity are labor supervision, skilled labor, availability of materials, availability of equipments and scheduling of work. Therefore, focus should be targeted on these factors to make the construction firms profitable as well as improving the progress in construction works.